2020
DOI: 10.1177/0272431620950469
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Emotional Eating During Early Adolescence and Associations With Appearance Teasing by Parents and Peers, Rejection, Victimization, Depression, and Social Anxiety

Abstract: Emotional eating, defined as eating in response to affect, may increase during early adolescence, a time of heightened emotionality and increased prevalence of emotional disorders. We investigated change in emotional eating, while also testing the influence of social–emotional risk factors. Study participants ( N = 379, mean age [ Mage] = 12.0 years; 56% girls) completed measures of emotional eating twice over 1 year and reported on social adversity within peer and parent contexts (i.e., appearance teasing by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 69 publications
1
19
0
Order By: Relevance
“…Numerous subsequent studies have confirmed that being teased about one’s weight by family members is related to adolescent binge eating behavior and disordered eating [ 23 , 24 ]. A 5-year longitudinal study of 2516 adolescents in the United States revealed that adolescents with dieting peers were more likely to engage in extreme weight control behaviors [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous subsequent studies have confirmed that being teased about one’s weight by family members is related to adolescent binge eating behavior and disordered eating [ 23 , 24 ]. A 5-year longitudinal study of 2516 adolescents in the United States revealed that adolescents with dieting peers were more likely to engage in extreme weight control behaviors [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may suggest that other influences are promoting the development of EE during adolescence (eg, external influences such as appearance teasing by peers or parents or internal influences such as social anxiety or body dissatisfaction). 55,56 The results of this study suggest that adolescents' characteristics, especially ER, play a considerable role in adolescents' EE. The correlation results showed that maladaptive ER was positively associated with adolescents' EE.…”
Section: Discussionmentioning
confidence: 73%
“…Depressive symptoms were measured with the 13‐item Short Mood and Feelings Questionnaire (Angold et al, 1995; e.g., “I felt I was no good anymore”). As has been done in previous research with adolescents (Webb et al, 2021), students were prompted to report their feelings within the past 2 weeks. Item responses ranged from 1 ( not true ) to 5 ( very true ).…”
Section: Methodsmentioning
confidence: 99%